Effects of Financial Literacy and Financial Behavior on Financial Well-Being: Meta-Analytical Review of Experimental Studies - Phaktada Choowan; Hanvedes Daovisan; Charin Suwanwong (International Journal of Financial Studies)
The purpose of this meta-analytical review of experimental studies was to examine the effects of financial literacy and financial behavior on financial well-being. This research was conducted by a master’s in library and information science (MLIS)-trained Information Specialist using the PICO framework. Of the 3089 publications identified, 415 studies were assessed for eligibility, and 9 articles met the inclusion criteria. The meta-analytical review of the selected studies was performed using a two-level model of the MAJOR module for JAMOVI 2020. The potential effect size of the intervention studies was 0.75, indicating the heterogeneity between groups in terms of financial literacy, which rejected the null hypothesis in favor of the alternative hypothesis. The theoretical and practical implications, strengths and limitations, and possibilities for future research were also addressed in this meta-analysis.